Short-Term Impact of COVID-19 Pandemic in Indonesian Stock Prices - Nugroho, Ahmad Cahyo; Herlambang, Sigit; Gusnanto, Arief (JDM (Jurnal Dinamika Manajemen), 2022)
The Indonesian stock market is unique because of its economic relations with China and the United States, the world’s two biggest economies that are severely impacted by the COVID-19 pandemic. This study examines the short-term impact of the COVID-19 pandemic on stock price movements on the Indonesian stock exchange. Our investigation identifies patterns of market responses in terms of stock price movements in the period. We find that the outbreak has affected, in terms of market response, the manufacturing and non-manufacturing stocks similarly. The impact of the outbreak seems to be felt by almost all economic sectors in a similar way. However, based on the result, the investors’ perception of the finance sector is more favorable relative to the other sectors during the pandemic. Several stocks identified have the potential to re-bounce if market conditions return to normal.